Extraction of Gas from Underground Gas Storage and its Technical and Economic Indicators - Egamnazarova Fazilat Dustkobilovna (European Science Publishing, 2024)
Gas extraction during the operation of the underground gas storage is determined based on the gas consumption graph. According to the location and security requirements, the underground gas storage will be located at some distance from the gas consumption area. The gas taken from the warehouse can be delivered to consumers using its own pressure or compressors.
Keywords: underground reservoirs, well-compressors, gas storage collector, gas loss to the atmosphere, diaphragm flow meters, optimization.